Qualitative Exploration of Farm to School Program Adoption and Expansion in Massachusetts Schools. Issue 2 (3rd March 2020) - Lehnerd, Megan E.; Goldberg, Jeanne P.; Folta, Sara C.; Cash, Sean B.; Griffin, Timothy S.; Lucas, Rebecca; Sacheck, Jennifer M.
ABSTRACT: Limited research has examined the rapid growth of farm to school (FTS) programs in the US. Qualitative interviews (n = 24) framed by Diffusion of Innovations theory were used to explore FTS program adoption and expansion in Massachusetts. Program compatibility and relative advantages related to academics, school meal participation, and child health motivated initial engagement. Active classroom integration, implementation simplification, and strong support networks aided program expansion. Leadership and sustainability plans, garden maintenance partnerships, and Community Eligibility Provision participation hold promise to help further program diffusion. Future research should focus on providing additional evidence for FTS aspects salient to adoption and expansion.